2021
DOI: 10.3390/ma15010195
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Conditioning on PU Foam Matrix Materials Properties

Abstract: This article deals with the characterization of the thermal-induced aging of soft polyurethane (PU) foams. There are studied thermal and mechanical properties by means of thermal analysis, tensile, compression and dynamic mechanical vibration testing. It was found in this study, that the increasing relative humidity of the surrounding atmosphere leads to the initiation of the degradation processes. This is reflected in the observed decreased mechanical stiffness. It is attributed to the plasticization of the P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 30 publications
(35 reference statements)
0
6
0
Order By: Relevance
“…Lapčík et al have indeed found that increased humidity causes initiation of degradation. [46] Like the tangent modulus, the PR shown in Figure 7d of both the 92% RH pristine and auxetic samples seem to be separated from the other specimens, despite the 15% RH pristine samples making this separation less obvious (Figure 7b). All values of the PR for the pristine samples are positive and the auxetic samples all show an NPR for most of the strain range.…”
Section: Quasi-static Compressionmentioning
confidence: 88%
See 1 more Smart Citation
“…Lapčík et al have indeed found that increased humidity causes initiation of degradation. [46] Like the tangent modulus, the PR shown in Figure 7d of both the 92% RH pristine and auxetic samples seem to be separated from the other specimens, despite the 15% RH pristine samples making this separation less obvious (Figure 7b). All values of the PR for the pristine samples are positive and the auxetic samples all show an NPR for most of the strain range.…”
Section: Quasi-static Compressionmentioning
confidence: 88%
“…Lapčík et al have recently investigated the effect of thermal and humidity conditioning on pristine PU foams. [ 46 ] Those authors found that conditioned foams became more compliant as the increased humidity caused the initiation of the degradation process. This shows the importance of similar testing on auxetic foams.…”
Section: Introductionmentioning
confidence: 99%
“…To give a response to mechanical compression, PU foam presents a light structure, with empty cell matrix geometry, that easily collapses under low-pressure regimes. 24 In recent years, PU foam has been widely used in e-skin for pressure detection due to its excellent elasticity, heat resistance, and biological harmlessness. 25 Huang et al 23 fabricated 3D lightweight piezoresistive sensing materials via surface coating the PU foam with hybrid CNT/ carbon black (CB) nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…CNTs can be directly deposited on the surfaces of various polymer materials by solution processing technology, which is very important for the simplicity of the process. , Flexible and elastic polyurethane (PU) foam provides great advantages in the manufacture of pressure sensors. To give a response to mechanical compression, PU foam presents a light structure, with empty cell matrix geometry, that easily collapses under low-pressure regimes . In recent years, PU foam has been widely used in e-skin for pressure detection due to its excellent elasticity, heat resistance, and biological harmlessness. Huang et al fabricated 3D lightweight piezoresistive sensing materials via surface coating the PU foam with hybrid CNT/carbon black (CB) nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of conditioning on the vibration damping of polyurethane (PU) foams, which were subjected to conditioning at two different temperatures (45 and 80 • C) and relative humidity values (45 and 80%) for different time intervals, was evaluated in [5]. It was found that the conditioning process had a significant influence on the properties of the tested PU foams.…”
mentioning
confidence: 99%